2010
DOI: 10.1177/1545109710367519
|View full text |Cite
|
Sign up to set email alerts
|

A Dedicated Screening Program for Geriatric HIV-Infected Patients Integrating HIV and Geriatric Care

Abstract: Background: Clinicians caring for HIV-infected patients >60 years old encounter multiple clinical challenges. The use of a functional geriatrics screening for detection of significant comorbidities is important in this population. Methods: The geriatrics screening evaluated functional capabilities, depression, cognitive dysfunction, nutrition, mobility, medicines used, and interactions. Results: As of July 2009, 57 patients were screened (average age 62.6, 39 males and 18 females). A total of 17 patients (9 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Although it is difficult to make direct comparisons, for context on our RE-AIM findings, in terms of reach, the geriatric-HIV program in New Orleans (Mmutu Clinic) saw 60 of 160 eligible patients age 60 in 1 year; the Over 50 clinic in London saw 150 patients over 2 years, and the Center for Special Studies program in New York City saw 76 patients over 4 years (2800 patients all ages). [24][25][26] The Center for Special Services program in New York reported that 7 of 10 providers found geriatric consultations very or extremely useful, which similar to our results suggest that providers find services valuable. 26 Another strength of using the RE-AIM framework in our evaluation is it provides a structure to organize key findings and how these findings might be applied or adapted to other settings.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although it is difficult to make direct comparisons, for context on our RE-AIM findings, in terms of reach, the geriatric-HIV program in New Orleans (Mmutu Clinic) saw 60 of 160 eligible patients age 60 in 1 year; the Over 50 clinic in London saw 150 patients over 2 years, and the Center for Special Studies program in New York City saw 76 patients over 4 years (2800 patients all ages). [24][25][26] The Center for Special Services program in New York reported that 7 of 10 providers found geriatric consultations very or extremely useful, which similar to our results suggest that providers find services valuable. 26 Another strength of using the RE-AIM framework in our evaluation is it provides a structure to organize key findings and how these findings might be applied or adapted to other settings.…”
Section: Discussionsupporting
confidence: 85%
“… 23 Examples of consultative models include a geriatrician-led weekly consultative clinic embedded in an HIV clinic (Center for Special Services clinic in New York City); an interdisciplinary review of geriatric screening results by a team comprised of a physician with geriatrics and infectious disease expertise, a pharmacist, a social worker, and a nurse practitioner (former Mmutu Clinic in New Orleans); and a separate, dedicated referral clinic consisting of an HIV consultant, nurse practitioner, pharmacist, and nutritionist (Over 50 clinic in London). 20 , 23 - 25 Although 3 clinics (New York, New Orleans, London) have program descriptions reported in the literature, empirical data on such programs are lacking, especially program evaluation data. 25 - 27 Few short-term outcomes are described, and we are unaware of data on concepts such as program acceptability, which is important for long-term programmatic success.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review conducted in our clinic found almost thirty (30%) percent of HIV-infected patients >60 years presented with a geriatric dysfunction after initial rapid screening. 27 This study confirms the high frequency of several conditions including hypertension, dyslipidemia, liver disease, diabetes, cardiovascular disease, mental health problems, chronic pain, and substance use among seniors with HIV. Our study is the first to explore possible sex and race differences in vulnerability for selected conditions and outcomes in an elderly HIV-infected population.…”
Section: Discussionsupporting
confidence: 79%
“…HIV-positive older people are more likely to have multiple complications arising from infection and require more frequent screening than younger HIV-positive patients. 84 The clinical implications of HIV-infected older people are complex as the addition of antiretroviral treatment into old age polypharmacy can cause additional complications. 85 The issues arising from the interaction of HIV and immunosenescence represent a growing problem which will require new strategies and further research to improve the health of this vulnerable group of patients.…”
Section: Infection In Older Agementioning
confidence: 99%